DNA Barcoding: Mixed results for big-headed flies (Diptera: Pipunculidae) - Skevington, Jeffrey H.; Kehlmaier, Christian; Ståhls, Gunilla (Zootaxa, 2007)
Sequence data from 658 base pairs of mitochondrial cytochrome c oxidase I (cox1) were analysed for 28 described species of Pipunculidae (Diptera) in an effort to test the concept of DNA Barcoding on this family. Two recently revised but distantly related pipunculid lineages with presumed different evolutionary histories were used for the test (Clistoabdominalis Skevington, 2001 and Nephrocerus Zetterstedt, 1838). An effort was made to test the concept using sister taxa and morphologically similar sibling species swarms in these two genera. Morphological species concepts for Clistoabdominalis taxa were either supported by cox1 data or found to be too broad. Most of the discordance could be accounted for after reassessing morphological characters. In these cases, the molecular data were invaluable in assisting taxonomic decision-making. The radiation of Nearctic species of Nephrocerus could not be diagnosed using cox1. The ability of cox1 to recover phylogenetic signal was also tested on Clistoabdominalis. Morphological data for Clistoabdominalis were combined with the molecular data set. The pipunculid phylogeny from molecular data closely resembles the published phylogeny based on morphology. Partitioned Bremer support is used to localize areas of conflict between the datasets.